Model Pembelajaran Pendidikan Jasmani di SD: Guru sebagai Perancang Program - M. Furqon Hidayatullah (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2003)
Teacher has a role not only as an executor but also as a designer of instruction. The purpose of this instructional model is to know how to design an instructional program of physical education with an approach enabling the teacher to be the designer of the instructional program in primary school. The steps for designing the instructional program are: setting the goal of instructional program; the instructional program suited with the phase of students’ growth and development; analyzing and selecting the elements of motor ability; selecting the elements of physical ability; analyzing the effect of the motor ability elements; and designing the instruction in the form of game or circuit.